Configuration and coordination of activities within a supply chain: exploring the synergy between modularity and information technology. (6th February 2006) - Kim, Ki-Chan; Sohn, Changsoo; Roemer, Thomas; Yassine, Ali
This research studies the impact of information technology-enabled coordination on product modularisation in the automotive industry. A structural equation model is tested based on 177 responses to questionnaires from 177 Korean first-tier automotive suppliers. The results provide support for the hypothesis that high quality of exchanged information enables better supply chain coordination, which in turn supports product modularisation.